2021
DOI: 10.3390/w13243489
|View full text |Cite
|
Sign up to set email alerts
|

Development of Boosted Machine Learning Models for Estimating Daily Reference Evapotranspiration and Comparison with Empirical Approaches

Abstract: Proper irrigation scheduling and agricultural water management require a precise estimation of crop water requirement. In practice, reference evapotranspiration (ETo) is firstly estimated, and used further to calculate the evapotranspiration of each crop. In this study, two new coupled models were developed for estimating daily ETo. Two optimization algorithms, the shuffled frog-leaping algorithm (SFLA) and invasive weed optimization (IWO), were coupled on an adaptive neuro-fuzzy inference system (ANFIS) to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…Similar results were obtained by using the same input combinations during the testing phase at all 10 stations, as indicated in Tables S1-S9. The results are in accordance with the findings of previous studies (dos Santos Farias et al 2020;Mehdizadeh et al 2021;Elbeltagi et al 2022a, b), which revealed that the use of all climatic variables in the models led to higher prediction accuracies.…”
Section: Effects Of Input Variables On Model Performance Across 10 St...supporting
confidence: 93%
“…Similar results were obtained by using the same input combinations during the testing phase at all 10 stations, as indicated in Tables S1-S9. The results are in accordance with the findings of previous studies (dos Santos Farias et al 2020;Mehdizadeh et al 2021;Elbeltagi et al 2022a, b), which revealed that the use of all climatic variables in the models led to higher prediction accuracies.…”
Section: Effects Of Input Variables On Model Performance Across 10 St...supporting
confidence: 93%
“…Wang et al, 2022)(Mehdizadeh et al, 2021)(Aghelpour et al, 2022)(Kadkhodazadeh et al, 2022)(Adnan et al, 2021). These investigations have demonstrated the effectiveness of combining AI techniques for the accurate prediction of ETo, which aligns with the ndings of the present study.…”
supporting
confidence: 91%
“…This can be explained by the ability of selected models to autonomously solve complex and nonlinear problems by gathering datasets from various sources [70]. The models' performance improved with an increasing number of input variables [42]. The greatest positive impact on the models' performance was observed when the crop coefficient data were added to weather data availability (scenario 2).…”
Section: Discussionmentioning
confidence: 99%
“…Today, these interactions can be successfully described by modern mathematical tools, including the application of machine learning methods. In the last few years, various machine learning methods have been tested to estimate both reference and crop ET [35][36][37][38][39][40][41][42][43][44]. In particular, these methods have been developed to enhance the prediction accuracy for the estimation of ETo with limited data availability and ETc under optimal water supply.…”
Section: Introductionmentioning
confidence: 99%